BOLD MRI and early impairment of cerebrovascular reserve after aneurysmal subarachnoid hemorrhage. Issue 4 (15th November 2013) - da Costa, Leodante; Fierstra, Jorn; Fisher, Joseph A.; Mikulis, David J.; Han, Jay S.; Tymianski, Michael
<x xml:space="preserve">Abstract</x> Currently no biological or radiological marker is available to identify patients at risk of delayed ischemic deficit (DIND) after aneurysmal subarachnoid hemorrhage (aSAH). We hypothesized whether MR‐based quantitative assessment of cerebrovascular reserve (CVR) would detect early radiological markers of vasospasm and DIND. This manuscript describes our initial experience with this population. Five patients with aSAH underwent blood‐oxygen level dependent‐MRI (BOLD‐MRI) with CO2 challenge for assessment of whole brain CVR. Patients were examined as soon as possible after aneurysm treatment. We obtained good quality anatomical and functional images without complications. Initial anatomical cerebrovascular imaging showed no vasospasm in all patients. Two patients had abnormal CVR‐MRI tests and both developed DIND. Of the 3 others with normal CVR‐MRI, one developed posterior circulation DIND. One patient with a normal CVR‐MRI developed angiographic vasospasm but no DIND. Changes in CVR maps as early as 36 h after hemorrhage had good spatial correlation with delayed ischemia during short‐term follow‐up. Our series shows that MRI with CO2 challenge is feasible in this difficult population. Further developments might allow BOLD‐MRI with CO2 challenge to identify patients at risk and provide anatomical correlation with future DIND, opening a new venue for prophylactic treatments. Further study is warranted in a larger patient cohort. J. Magn. Reson. Imaging 2014;40:972–979. © 2013 Wiley Periodicals, Inc.